Embedded Through-Section shear strengthening technique using steel and CFRP bars in RC beams of different percentage of existing stirrups - Breveglieri, M. (2015)
The Embedded Through-Section (ETS) technique is a promising technique for the shear strengthening of existing (RC) elements. According to this technique, holes are drilled through the beam section, and bars of steel or FRP material are introduced into these holes and bonded to the concrete with adhesive materials. An experimental program was carried out with RC T-cross section beams strengthened in shear using the ETS steel bars and ETS CFRP rods. The research is focused on the evaluation of the ETS efficiency on beams with different percentage of existing internal transverse reinforcement (ρsw=0.0%, ρsw=0.1% and ρsw=0.17%). The effectiveness of different ETS strengthening configurations was also investigated. The good bond between the strengthening ETS bars and the surrounding concrete allowed the yield initiation of the ETS steel bars and the attainment of high tensile strains in the ETS CFPR rods, leading to significant increase of shear capacity, whose level was strongly influenced by the inclination of the ETS bars and the percentage of internal transverse reinforcement.